Regulating Labour Migration in the Republic of Uzbekistan - A. A. Mamatkhanov (Plekhanov Russian University of Economics, 2020)
International migration, in particular migration of labour resources plays an important role both for migrants themselves as participants of international division of labour and for countries of departure and destination, especially from the point of view of economic development. We know the positive impact of labour migration for countries of departure as a labour resource donor, when migrants send considerable cash to their native land, which improves the standard of living of members of their households and provides access to key social welfare and services, such as education and Public health service, food. However, issues dealing with regulation of migration processes in Uzbekistan are still topical and the latest attempts to settle them were useless. At the same time Russia as a key partner of Uzbekistan in migration exchange of labour resources, as a country of destination is taking first steps to liberalize migration legislation and is ready to take other decisions to simplify the procedure of granting its citizenship to more and more people (citizens of the CIS). Uzbekistan in the medium- range of time will have an excess amount of labour resource, which can be used in Russia but for building the strong foundation of social protection of Uzbek migrants it is necessary to develop local legislative basis and international agreements. The author provides recommendations aimed at designing migration policy to ensure stable economic growth in Uzbekistan and sustainability of its public system.